30-seconds (1 Km2) gridded Future Climate Change Scenarios for Honduras - Navarro Racienes, Carlos Eduardo; Monserrate Rojas, Fredy Alexander (International Center for Tropical Agriculture, 2018)
Future climate change scenarios for Honduras were developed by downscaling CMIP5 projections from 18 General Circulation Models (GCMs) for four Representative Concentration Pathways (RCP’s; RCP 2.6, 4.5, 6.0, and 8.5; IPCC, 2013) and three future periods named as 2030s (Climatic normal –CN- for 2021 to 2050), 2050s (CN for 2041-2070) and 2080s (CN for 2071 to 2100).